Pollen-derived vegetation reconstruction at IODP Site 353-U1446, Bay of Bengal - Zorzi, Coralie; Desprat, Stéphanie; Clément, Charlotte; Thirumalai, Kaustubh; Oliviera, Dulce; Anupama, Krishnamurthy; Prasad, Srinivasan; Martinez, Philippe (PANGAEA, 2022)
This data set presents the composition of vegetation in the Mahanadi Basin during the Last Glacial Period (80-20 ka). Percentages of the tropical trees, the arid-taxa, Artemisia, Poaceae and Cyperaceae recorded at IODP Site U1446 (19°5'N, 85°4'E, 1430 m water depth) are shown, as well the Diversity Simpson's index based on pollen record and the Axis 1 sample scores of the Principal Component Analysis, which is used in this study as humidity index (Figures 2 and 3 of the related study). This data set also contained the confidence intervals shown in Figure S10 and the row pollen data. We also included labels, depth (in m CCSF-A) and estimated age (Ka) of the studied samples.
Keywords: Bay of Bengal; Indian Summer Monsoon; Last glacial period; Mahanadi Basin; pollen analysis; Vegetation composition